Toronto 1919 - Naylor, James (Historical Papers / Communications historiques, 1986)
AbstractIn their examination of the conflicts which followed the First World War, Canadian labour historians have tended to draw a sharp dichotomy between a “radical” west and a “conservative” east. Events in Toronto, however, which brought the city to the edge of a general sympathetic strike in late May 1919 cannot be explained in this way. The most notable feature of the Toronto labour movement was the degree of polarization within it. The potential clearly existed for a break with past forms of craft organization, towards a highly politicized industrial unionism. A powerful left wing, with wide support among newly organized, less-skilled workers, as well as workers with an immediate need for new forms of organization, was rapidly gaining dominance in the central bodies of the Toronto labour movement. Opposing them were the major beneficiaries of previous waves of organizing. These consisted, on the one hand, of union leaders who had helped shape the Toronto labour movement, and found key places for themselves within it. On the other hand, it also included a large number of workers who had established a stable bargaining relationship with employers, and a stake in the benefits their organizations had given them. This division meant that, from the outset, the possibilities for the establishment of a “One Big Union” did not exist, despite the enthusiasm that the western movement initially generated in Toronto. Conservative unions and leaders lost their dominance within the city's central union bodies but, by foiling the sympathetic general strike, were able to prevent the radicals from implementing an alternative strategy.